Problem-based Learning in Undergraduate Dental Education: Faculty Development at the University of Southern California School of Dentistry - Timothy R. Saunders, DDS;1 and Shireen Dejbakhsh, DDS2 (Journal of Prosthodontics, 2007)
The University of Southern California School of Dentistry (USCSD) seeks to educate oral health professionals with a balanced curriculum covering health promotion, risk assessment and disease prevention, diagnostics, treatments, and therapeutics.